NAVIGATING REHABILITATION OF MANUAL SCAVENGERS WITH REFERENCE TO MEASURES UNDER THE THE EMPLOYMENT OF MANUAL SCAVENGERS AND CONSTRUCTION OF DRY LATRINES (PROHIBITION) ACT, 1993 & THE PROHIBITION OF EMPLOYMENT AS MANUAL SCAVENGERS AND THEIR REHABILITATION - R. Dhivya; Rao, B. Someswara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Manual Scavenging is another form of slavery and forcing the human to lead their life by doing this from generation to generation.Throughout history, Manual scavenging has been connected with caste in India. It is another form of caste discrimination that has existed in India for ages. Manual scavenging is a serious socio-legal issue that violates human dignity and all standards of decent employment. It becomes essential to recognise that manual scavenging is a kind of caste-based violence in and of itself. It is one of the most abhorrent realities that exist in the nation today . In order to lead their life in a dignified manner everyone needs a livelihood that’s where employment steps in. Identifying and rehabilitation of manual scavengers makes a path to the eradication of manual scavenging in India. The Manual Scavengers Act, 1993 & 2013 expresses strong commitment towards rehabilitation of Manual Scavengers and employment measures for Manual Scavengers In India. This paper aims to navigate the rehabilitation ,measures and schemes of Manual Scavengers and its impact on the right to employment of Manual Scavengers in India.